Defectors and the Liberal Party 1910-2010 : a study of inter-party relations (MANCHESTER UNIV Press, 2017)
This book is the first analysis of political defections over a long time span. It investigates all the Liberal/Liberal Democrat MPs and former MPs who defected from the party between the elections of December 1910 and May 2010 - around one sixth of all those elected - as well as the smaller number of inward defectors. Each of the 122 defections was an expert judgment on the state of the party at a specific date. The research investigates the timing and reasons for all the defections and reveals long-term trends and underlying causes and apportions responsibility between leaders for them. The a.